Achalasia in a Female Adolescent - Kukuh Rizwido Prasetyo; Yudi Suryana (Cermin Dunia Kedokteran, 2023)
Achalasia is an esophageal smooth muscle motility disorder due to relaxation failure of the lower esophageal sphincter. This condition is rarely found in children; 2-5% cases occur in less than 16-year old. Case: A 16-year-old girl presented with chief complaint of regurgitation. She also complained of dysphagia, weight loss, and general weakness. Her general appearance was weak, underweight, and decreased skin turgor. Barium esophagogram demonstrated a narrowing of esophagus lumen distal to the esophagogastric junction with a “bird’s beak” appearance or rat tail sign. Esophageal achalasia was diagnosed and managed with open (laparotomy) surgical myotomy and fundoplication. Post-operative diet arrangement was carried out gradually and the patient was discharged 4 days post-surgery. Akalasia merupakan gangguan motilitas otot polos esofagus yang terjadi akibat kegagalan relaksasi lower esophageal sphincter (LES). Kondisi ini jarang ditemukan pada anak-anak; 2-5% kasus pada anak berusia di bawah 16 tahun. Kasus: Seorang remaja perempuan 16 tahun datang ke poliklinik bedah anak dengan keluhan utama regurgitasi. Anak juga mengeluh disfagia, penurunan berat badan, dan kelemahan umum. Keadaan umum anak lemah, berat badan rendah, dan penurunan turgor kulit. Esofagogram barium menunjukkan penyempitan lumen esofagus distal terhadap esophagogastric junction dengan tampakan “bird’s beak” atau tanda rat tail. Akalasia esofagus didiagnosis dan ditatalaksana dengan pembedahan laparotomi miotomi dan fundoplikasi. Pemulihan diet pasca-operasi secara perlahan dan pasien dipulangkan 4 hari pasca pembedahan